Evidence of maternal transfer of antigen-specific antibodies in serum and breast milk to infants at high-risk of S. pneumoniae and H. influenzae disease - Martinovich, Kelly M.; Seppanen, Elke J.; Bleakley, Amy S.; Clark, Sharon L.; Andrews, Ross M.; Richmond, Peter C.; Binks, Michael J.; Thornton, Ruth B.; Kirkham, Lea-Ann S. (Frontiers in Immunology, 2022)
Introduction:Children living in low-mid income countries, and First Nations children living in high-income countries, experience disproportionately high rates of Streptococcus pneumoniae and Haemophilus influenzae infections and diseases including pneumonia and otitis media. We previously observed that infants from Papua New Guinea had no evidence of waning maternal immunity for H. influenzae-specific antibodies. In this study, we assessed S. pneumoniae and H. influenzae antibody titres in Australian First Nation mothers and infants to determine antigen-specific antibody ontogenies and whether H. influenzae antibody titres in infants were due to low maternal antibody titres or lack of placental transfer. Methods:Breast milk, infant nasopharyngeal swabs and ear assessment data were collected 1-, 2-, 7-months post-birth as well as maternal, cord and 7-month-old infant sera, from 85 Australian Aboriginal and Torres Strait Islander mother-infant pairs. Serum IgG and breast milk IgG and IgA antibody titres to S. pneumoniae antigens (PspA1, PspA2, CbpA, Ply) and H. influenzae antigens (PD, ChimV4, OMP26, rsPilA) were measured. Results: IgG titres in maternal and cord were similar for all antigens, except Ply (higher in cord; p=0.004). Sera IgG titres at 7-months of age were lower than cord IgG titres for all S. pneumoniae antigens (p<0.001). Infant sera IgG titres were higher than cord for H. influenzae PD (p=0.029), similar for OMP26 (p=0.817) and rsPilA (p=0.290), and lower for ChimV4 (p=0.004). Breast milk titres were similar for all antigens at 1, 2 and 7-months except OMP26 IgA (lower at 7-months than 1-month; p=0.035), PspA2 IgG (p=0.012) and Ply IgG that increased by 7-months (p=0.032). One third of infants carried nontypable Haemophilus influenzae (NTHi), 45% carried S. pneumoniae and 52% had OM observed at least once over the 7-months. 73% of infants who carried either S. pneumoniae or NTHi, also had otitis media observed. Conclusions:Similarities between maternal and cord IgG titres, and absence of waning, support a lack of maternal H. influenzae IgG antibodies available for cross-placental transfer. Increased maternal anti-PD IgG could offer some protection from early carriage with NTHi, and maternal immunisation strategies should be considered for passive-active immunisation of infants to protect against S. pneumoniae and H. influenzae diseases.